Hypoxia-induced amniotic fluid stem cell secretome augments cardiomyocyte proliferation and enhances cardioprotective effects under hypoxic-ischemic conditions - Kukumberg, Marek; Phermthai, Tatsanee; Wichitwiengrat, Suparat; Wang, Xiaoyuan; Arjunan, Subramanian; Chong, Suet Yen; Fong, Chui-Yee; Wang, Jiong-Wei; Rufaihah, Abdul Jalil; Mattar, Citra Nurfarah Zaini (Scientific reports, 2021)
Secretome derived from human amniotic fluid stem cells (AFSC-S) is rich in soluble bioactive factors (SBF) and offers untapped therapeutic potential for regenerative medicine while avoiding putative cell-related complications. Characterization and optimal generation of AFSC-S remains challenging. We hypothesized that modulation of oxygen conditions during AFSC-S generation enriches SBF and confers enhanced regenerative and cardioprotective effects on cardiovascular cells. We collected secretome at 6-hourly intervals up to 30 h following incubation of AFSC in normoxic (21%O 2 , nAFSC-S) and hypoxic (1%O 2 , hAFSC-S) conditions. Proliferation of human adult cardiomyocytes (hCM) and umbilical cord endothelial cells (HUVEC) incubated with nAFSC-S or hAFSC-S were examined following culture in normoxia or hypoxia. Lower AFSC counts and richer protein content in AFSC-S were observed in hypoxia. Characterization of AFSC-S by multiplex immunoassay showed higher concentrations of pro-angiogenic and anti-inflammatory SBF. hCM demonstrated highest proliferation with 30h-hAFSC-S in hypoxic culture. The cardioprotective potential of concentrated 30h-hAFSC-S treatment was demonstrated in a myocardial ischemia–reperfusion injury mouse model by infarct size and cell apoptosis reduction and cell proliferation increase when compared to saline treatment controls. Thus, we project that hypoxic-generated AFSC-S, with higher pro-angiogenic and anti-inflammatory SBF, can be harnessed and refined for tailored regenerative applications in ischemic cardiovascular disease.